Skogsägarenas inställning till markberedning i västra Värmland - Andersson, Andreas (SLU/School for Forest Management, 2014)
According to a press release from the Swedish forest agency in May 2014, western Värmland has the worst regenerations of forest result in the whole of Sweden. The scarification frequency is low in the area. AB Hilmer Andersson want´s to know if the private forest owners want to scarify more than is done today. Good regeneration is important for private forest owners so they can have a long term forest management and economics of their forests. This academic study is done as an opinion poll. The purpose of the study is to see how big the interest of scarification among the private forest owner is. The questionnaire was sent to 200 private forest owners who have sold timber to AB Hilmer Andersson in the past, 132 of them answered the 19 questions in the survey. This makes a response rate of 66 %. The result of the survey shows that the private forest owners want to scarify more forest land than they do today. The overall interest for scarification follows how much forest land the forest owner has. The group that owns the smallest forest estates (under 30 hectares) had the lowest interest and the group that owns the biggest forest estates (over 100 hectares) had the biggest overall interest in scarification. The biggest knowledge source for forest owners is information from a forest officer. It was substantially the women that use this source of knowledge. This shows that the timber buyers have a big responsibility to make the private forest owners make the right decision. About half of the private forest owners answered that they want to scarify more than they do today. The biggest reason for not scarifying is the cost and too small clean cuts.